SCIENTIFIC APPROACHES TO THE GREENING THE TECHNOLOGY OF GROWING SPRING BARLEY IN CONDITIONS OF THE LEFT – BANK FOREST-STEPPE - Gorobets, M. V.; Pysarenko, P. V.; Chaika, T. O.; Mishchenko, O. V. (Scientific Progress & Innovations, 2020)
The potential negative consequences of climate change in the conditions of the Left – Bank Forest – Steppe are analyzed and it is said that the main potential negative consequences of climate change, which can be manifested at the present time, are thermal stress; flooding; reduction of areas and violation of the species composition of green areas; natural hydrometeorological phenomena; reducing the amount and deterioration of drinking water. It is emphasized that there is a clear increase in air temperature in Ukraine over the period of 1996–2016. A characteristic assessment of spring barley as a promising grain crop as an important one for the full food security of Ukraine, because it belongs to the crops of universal use, is given. The influence of the varietal properties of the plants themselves and the timely use of stimulants are important to obtain high and stable yields of spring barley. On the example of a control field with an area of 100 hectares, which belongs to AH “Gorobets” in Shilivka village, Reshetyliv district, Poltava region, the methods of greening the technology of growing spring barley and increase its yield by using stimulants such as bischofite solution, Epin – extra, Zircon and Polystin were evaluated. The experiment was performed for such varieties of spring barley as Helios, Vakula, Parnassus and included treatment of the studied varieties of spring barley with a solution of bischofite with different concentrations and without treatment (control). The soil of the experimental site is gray forest, heavy loamy in terms of granulometric composition. It has been experimentally established that a solution with a bischofite concentration of 1.0 % has an optimal stimulating effect on the germination of spring barley seeds, and the bischofite itself has a complex effect on plants of twenty macro- and microelements contained in bischofite. When processing spring barley on sod – podzolic soil spraying crops in the tillering phase with growth regulators Epin-extra, Zircon and Polystin, the duration of plant development phases was reduced as well as the growing season by 2–4 days, which allows to start harvesting barley for grain earlier than usual. The use of stimulants Epin-extra and Polystin increases the assimilation surface of the leaves of spring barley crops by 8.5 and 11.1%, respectively; photosynthetic potential by 6.2 % and net productivity of photosynthesis on average during the growing season by 3.3 and 10.4 %, respectively. The use of the Zircon stimulator in the tillering phase does not have a significant positive effect on the photosynthetic activity of spring barley crops in soil and climatic conditions.